Art After Democracy, Art Before Democracy - Mizerkiewicz, Tomasz (Poznańskie Studia Slawistyczne, 2019)
The paper describes today’s new situation of art facing antidemocratic processes. The powerful metaphor of Parthenon of books is used, which once was the name of an installation by Marta Minujín presented just after the fall of Argentinian brutal regime in the early eighties and reinstalled again few years ago. The author points that popular “posts” of humanities (postmodernism, postsecularism etc.) need to be replaced by the philosophy of art being after some definite change. The new temporal and public condition of art being after is the result of its dramatic contemporary and future challenges.